The First Darwinian: Alfred Russel Wallace and the Meaning of Darwinism. (21st October 2019) - Hesketh, Ian
Abstract: This essay is an initial study of a larger project that seeks to produce a history of the term 'Darwinism'. While it is generally well-known that Darwinism could refer to a variety of different things in the Victorian period, from a general evolutionary naturalism to the particular theory of natural selection, very little has been written about the history of the term or how it was contested at given times and places. Building on James Moore's 1991 sketch of the history of Darwinism in the 1860s, this paper specifically seeks to situate Alfred Russel Wallace's 1889 book Darwinism in the context of a larger struggle over Darwin's legacy in the 1880s. It is argued that Wallace used his authority as one of the founders of evolution by natural selection to reimagine what he called 'pure Darwinism' as a teleological evolutionism, one that integrated the theory of natural selection with an interpretation of spirit phenomena thereby producing a more agreeable and holistic account of life than was previously associated with Darwinian evolution. By considering the reception of Wallace's Darwinism in the periodical press it will be argued further that Wallace's interpretation of Darwinism was generally well received, which suggests that our understanding of what Darwinism meant in the late Victorian period needs to be revisited.